Analisis Pengukuran Kinerja Perusahaan dengan Menggunakan Konsep Balanced Scorecard Pada PT. BPR Sari Sedana - Pika, Putu Ayu Titha Paramita; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
The purpose of this study is to know and analyze the performance of PT. BPR Sari Sedana using balanced scorecard concept consisting of financial perspective, customer, internal business process and learning and growth. The number of customers who are sampled using slovin formula is 85 people with simple random sampling technique and the number of employees sampled is 15 people with saturated sampling technique. The results of this study obtained that the performance of PT. BPR Sari Sedana from a financial perspective, customer perspective and learning and growth perspective is good, while on the internal business process perspective is good enough. Based on these results, PT. BPR Sari Sedana is expected to plan the right strategy in the future to improve its performance primarily in the perspective of its internal business processes and from the four balanced scorecard perspectives is expected to contribute in its performance measurement. Keywords : balanced scorecard, financial perspective, customer perspective, internal business process perspective, learning and growth perspective